Cryptobiometrics for the Generation of Cancellable Symmetric and Asymmetric Ciphers with Perfect Secrecy - Vicente Jara-Vera; Carmen Sánchez-Ávila (Mathematics, 2020)
Security objectives are the triad of confidentiality, integrity, and authentication, which may be extended with availability, utility, and control. In order to achieve these goals, cryptobiometrics is essential. It is desirable that a number of characteristics are further met, such as cancellation, irrevocability, unlinkability, irreversibility, variability, reliability, and biometric bit-length. To this end, we designed a cryptobiometrics system featuring the above-mentioned characteristics, in order to generate cryptographic keys and the rest of the elements of cryptographic schemes—both symmetric and asymmetric—from a biometric pattern or template, no matter the origin (i.e., face, fingerprint, voice, gait, behaviour, and so on). This system uses perfect substitution and transposition encryption, showing that there exist two systems with these features, not just one (i.e., the Vernam substitution cipher). We offer a practical application using voice biometrics by means of the Welch periodogram, in which we achieved the remarkable result of an equal error rate of (0.0631, 0.9361). Furthermore, by means of a constructed template, we were able to generate the prime value which specifies the elliptic curve describing all other data of the cryptographic scheme, including the private and public key, as well as the symmetric AES key shared between the templates of two users.